Influencing factors of depressive symptoms during pregnancy in Beijing, China - He, Xiayue; Wang, Xiaoqian; Li, Guoguang; Zhu, Simin; Wu, Yifan; Sun, Xiaotong; Wu, Yuze; Hu, Bo; Wu, Jianyin; Feng, Lina; Li, Guihong; Zhang, Lei; et al. (Frontiers in Psychiatry, 2025)
ObjectivePrenatal depression is a prevalent mental health challenge encountered during pregnancy and is notably associated with adverse maternal and neonatal outcomes. This study aimed to elucidate the likelihood and determinants of depressive symptoms among pregnant individuals in Beijing, thereby laying a foundational framework for the theoretical underpinning of prenatal screening and preemptive interventions for mental disorders.MethodsThe study dataset was derived from 4,564 pregnant individuals in Beijing utilizing a cross-sectional survey methodology. Data collection focused primarily on the personal and obstetric information of the participants. The Edinburgh Postnatal Depression Scale (EPDS) was employed as the primary screening tool to identify depressive symptoms.ResultsThe prevalence of depressive symptoms among the included pregnant individuals was 4.1%. The univariate analysis results revealed statistically significant differences in the incidence of depressive symptoms in women with different parities, numbers of births, medication use, numbers of abortions, prepregnancy weights, and body mass indices (BMIs) (the χ2 values were 61.130, 52.008, 23.291, 5.293, and 12.681, respectively; P<0.05). There were statistically significant differences in the incidence of depressive symptoms among women with different occupation types (χ2 = 30.263, P<0.01). The multivariate logistic regression analysis results revealed that a greater number of pregnancies, number of births, and BMI were risk factors for prenatal depression, whereas the commercial and service worker occupation types were protective factors against prenatal depression.ConclusionFuture directives should emphasize the enhancement of screening for depressive symptoms among pregnant individuals with greater parity and BMIs, alongside encouraging continued employment and flexible job selection. It is imperative to implement suitable intervention strategies for pregnant individuals exhibiting depressive symptoms to mitigate the incidence of adverse maternal and neonatal outcomes.